2013
DOI: 10.6026/97320630009094
|View full text |Cite
|
Sign up to set email alerts
|

Computational model for pathway reconstruction to unravel the evolutionary significance of melanin synthesis

Abstract: Melanogenesis is a complex multistep process of high molecular weight melanins production by hydroxylation and polymerization of polyphenols. Melanins have a wide range of applications other than being a sun - protection pigment. Melanogenesis pathway exists from prokaryotes to eukaryotes. It has evolved over years owing to the fact that the melanin pigment has different roles in diverse taxa of organisms. Melanin plays a pivotal role in the existence of certain bacteria and fungi whereas in higher organisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In microbial melanogenesis the most important enzyme seems to be tyrosinase, a monooxygenase which binds two copper ions within the active site by three conserved histidines residues [ 12 ]. Indeed, Liu et al [ 33 ] identified the heat-inducible tyrosinase responsible for the pigment production by wild B .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In microbial melanogenesis the most important enzyme seems to be tyrosinase, a monooxygenase which binds two copper ions within the active site by three conserved histidines residues [ 12 ]. Indeed, Liu et al [ 33 ] identified the heat-inducible tyrosinase responsible for the pigment production by wild B .…”
Section: Discussionmentioning
confidence: 99%
“…weihenstephanensis JAS 83/3 genome. Nevertheless, there are several other enzymes potentially involved in melanin production, such as laccase or polyketide synthases [ 12 , 13 , 17 ]. Also some species produce melanin in a way of homogentisic acid polymerization [ 14 , 53 ], yet little is known about these mechanisms among B .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic Information-This includes Gene name, Protein name, Uniprot id, status, Length of the protein, gene name synonyms and also the source from which this protein is obtained as vitiligo disease protein. This source can be related to protein or pathway in which the protein is involved like database, microarray experimentation, autoimmunity, susceptibility studies, apoptosis, melanogenesis (Singh et al, 2013) or oxidative stress.…”
Section: Vitiligo Protein Repositorymentioning
confidence: 99%
“…()). Melanogenesis is a complex multistep production of melanins via hydroxylation, oxidation, and polymerization of the oxidized metabolites (Singh, Malhotra, Pandey, & Pandey, ). To be specific, melanin biosynthesis in insect cuticle initially starts with tyrosine being converted to dopa by tyrosine hydroxylase (TH), and the dopa is directly used to produce dopa‐melanin pigments or further converted to dopamine with the action of dopa decarboxylase (DDC) and used to produce dopamine‐melanin pigments (Wright, ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%